Novel BODIPY-based Ru(ii) and Ir(iii) metalla-rectangles: cellular localization of compounds and their antiproliferative activities. Issue 23 (1st February 2016) - Gupta, Gajendra; Das, Abhishek; Ghate, Nikhil Baban; Kim, Takhyeon; Ryu, Ji Yeon; Lee, Junseong; Mandal, Nripendranath; Lee, Chang Yeon
Abstract : The synthesis and antiproliferative activities of novel BODIPY-based Ru and Ir rectangles are presented. Abstract : The first examples of Ru(ii) and Ir(iii) metalla-rectangles [1 ] 4+ –[4 ] 4+ containing a BODIPY-based linker are reported; some of these compounds exhibited highly selective anticancer activity and interact strongly with DNA as well as protein. The characteristic green fluorescence of a BODIPY ligand and associated aggregation-induced emission (AIE) permitted visualization of compounds inside the cells using confocal microscopy.